1999
DOI: 10.1080/01635589909514743
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen intake and prostate cancer: A case‐control study using a new database

Abstract: In the last several years, attention has been focused on comparing the Western diet, which is rich in fat, protein, and refined carbohydrates, with the Asian diet, which is rich in phytoestrogens, as a possible explanation for the contrasting rates of clinically relevant prostate cancer. Phytoestrogens, plant-derived nutrients, include several isoflavones, flavonoids, lignans, phytosterols, and coumestans, some of which have been postulated as having anticarcinogenic properties. Using a new database, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
3
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(135 citation statements)
references
References 27 publications
4
124
3
4
Order By: Relevance
“…In earlier observational studies, dietary intake of isoflavones or soy product consumption was inversely associated with prostate cancer risk in some (Severson et al, 1989;Jacobsen et al, 1998;Strom et al, 1999;Kolonel et al, 2000a;Lee et al, 2003;Sonoda et al, 2004;Hedelin et al, 2006a;Heald et al, 2007;Kurahashi et al, 2007;Nagata et al, 2007), but not all reports (Sung et al, 1999;Villeneuve Matching for geographic location (Hawaii or California), race/ethnicity, birth year ( ± 1 year), date ( ± 6 months) and time ( ± 2 h) of specimen collection, and fasting hours (0 -o6, 6 -o8, 8 -o10, and 10+ h). The models were adjusted for age at specimen collection and fasting hours as continuous variables, as well as family history of prostate cancer, BMI, and education.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier observational studies, dietary intake of isoflavones or soy product consumption was inversely associated with prostate cancer risk in some (Severson et al, 1989;Jacobsen et al, 1998;Strom et al, 1999;Kolonel et al, 2000a;Lee et al, 2003;Sonoda et al, 2004;Hedelin et al, 2006a;Heald et al, 2007;Kurahashi et al, 2007;Nagata et al, 2007), but not all reports (Sung et al, 1999;Villeneuve Matching for geographic location (Hawaii or California), race/ethnicity, birth year ( ± 1 year), date ( ± 6 months) and time ( ± 2 h) of specimen collection, and fasting hours (0 -o6, 6 -o8, 8 -o10, and 10+ h). The models were adjusted for age at specimen collection and fasting hours as continuous variables, as well as family history of prostate cancer, BMI, and education.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] According to a recent review article by Kolonel et al, 30 however, although early epidemiologic studies implicated dietary fat as a likely causal factor for this cancer, scientific support for such an association has [31][32][33][34][35][36] Soya is a major source of the isoflavonoids, daidzein and genistein. 33 According to Griffiths et al, 34 a Japanese male consumes approximately 20 mg of isoflavones per day, whereas Western men consume less than 1 mg/day.…”
Section: Prostatic Cancermentioning
confidence: 99%
“…A study in a multiethnic population showed a nonsignificant, protective effect of soy food consumption across Asian and non-Asian populations including Japanese, Chinese, African-American, and Caucasian men (Kolonel et al, 2000). A case-control study suggested a protective effect of soy isoflavones (Strom et al, 1999). It was proposed that the estrogen-like structure of isoflavones may interact with male steroid hormones and alter circulating sex hormone levels (Makela et al, 1991).…”
Section: Introductionmentioning
confidence: 99%